Matthew Calbraith Perry 1853-1854-es expedíciója Japánban (SZTE BTK Történész Diákkör, 2014)
A dokumentumok forrása: United States Senate: Executive Documents. 33rd Cong., 2nd. sess., 1854-1855, Vol. 6. Francis L. Hawks (szerk.): Narrative of the Expedition of an American Squadron to China and Japan, performed in the years 1852, 1853, and 1854, under the Command of Commodore M. C. Perry United States Navy, by Order of the Government of the United States. Vol. 1. A.O.P. Nicholson printer, Washington, 1865. 256-259. MeijiJapan through contemporary sources. Vol. 2, Centre for East Asian Cultural Studies, Tokyo, 1969. 15-16. Hunter Miller (szerk.): Treaties and Other International Acts of the United States of America. Vol. 6. Government Printing Office, Washington 1942. Sámuel Wells Williams (Frederick Wells Williams, szerk.): A Journal of the Perry Expedition to Japan. Kelly & Walsh, Yokohama, 1910. 246-248. Szakmailag és nyelvileg lektorálta: Kökény Andrea